The Relationship Between Mothers’ Level Of Knowledge And The Completion Of The Full Series Of Basic Immunizations (IDL) Among 12-Month-Old Infants In The Service Area Of The Tempurejo Community Health Center - Diah Shari Kusuma Anggraini; Riza Umami (CV. AFDIFAL MAJU BERKAH, 2026)
In Indonesia, there are still many babies who have not received complete immunizations or have never been immunized since birth. According to the Central Statistics Agency, the coverage of Complete Basic Immunization in East Java in 2023 reached 62.67%, in Jember 53.90% while at the Tempurejo Health Center 67.8%. Many factors hinder the immunization program, one of which is the lack of knowledge of mothers. Based on a preliminary study, it was found that most mothers brought their babies to the Posyandu just to be weighed. The purpose of the study was to determine the relationship of Mother’s Knowledge Level with Complete Basic Immunization Completeness in 12 Months Old Babies. This research is quantitative with an analytical observational design using a cross-sectional approach. Respondents were 39 people selected using purposive sampling techniques and analysis tests using Chi Square. The level of maternal knowledge was less than 41%, sufficient at 28.2%, and good at 30.8%, while basic immunization was incomplete at 53.8% and complete basic immunization at 46.2%. The results of the Chi Square test obtained a p-value of 0.001 < α (0.05), meaning there was a relationship between the level of maternal knowledge and the completeness of Complete Basic Immunization with a contingency coefficient value of 0.52 (moderate). The better a mother's knowledge, the higher the likelihood that her baby will receive complete basic immunizations. Midwives are expected to approach and educate mothers of toddlers about the importance of complete basic immunizations for infants, which are carried out routinely and continuously at every integrated health post.